Análise de cadeias coesivas em narrativas escritas por adolescentes com o transtorno do déficit de atenção hiperatividade - Lins, Selma Roseni (2007)
The disruption of the lack of attention/hyperactivity (Deficit de Atenção/Hiperatividade - TDAH) is a disease which is related to neurobehaviour and occurs specially in children and teenagers. Their main characteristics are inattention, hyperactivity and acting impulsively. One of the morbidities of this disease are the difficulties in writing. These difficulties are related to the problems people have to deal with sequence of letters, words, sentences and paragraphs, including difficulties in writing more complete texts. The writing production is not so effective in this case. This research observed texts written by teenagers with TDAH. People who have this disease attended a writing period of work trying to see their lexical cohesion. The research took place last year in Recife-PE between March and June and three 11-16 years-old teenagers, boys and girls, attended it. It was possible to see that those teenagers got to write cohesive texts. On the other hand, free subjects and some themes like texts for theater, texts built in group and short stories looked like to give them much more stimulation to write than subjects like music and movies.